The Legality Questioning of the Investigation Termination Through the Investigation Warranty on Corruption Crime - Silambi, Erni Dwita; Tajuddin, Mulyadi Alrianto; Rado, Rudini Hasyim; Y. Badilla, Nurul Widhanita (UNISSULA, 2024)
The ongoing investigation sheds light on a criminal case. The purpose of this study is to analyze the legality of the termination of the investigation of corruption cases carried out by the KPK as a result of the enactment of Article 40 of Law No. 30 of 2002. This research focuses on the authority of the KPK in stopping the investigation process of corruption crimes through the Investigation Termination Order (SP3). With the type of normative juridical-based research, the research is centered on literature research taken from the study of the election, literature studies, and other scientific works then analyzed using qualitative research methods that are oriented to the conceptual certainty approach and the case approach. The main problems found include the legality of SP3 by the KPK in corruption crimes. The results of the study show the position of the KPK as a super body institution, in the enforcement of corruption crimes, it has several special authorities because it is regulated in a specialist manner in its own provisions, including the authority to investigate based on philosophical, sociological, and juridical aspects, where the essence of the KPK's authority is a rational effort in eradicating corruption and realizing law enforcement oriented towards justice and legal certainty. The recommendation given is that investigations and investigations by the KPK must be carried out professionally, efficiently, and effectively by paying attention to the conditions that must be met before the investigation is carried out, so that synergy and coordination between law enforcement officials are needed.